Employment Past Trends and Prospects for 1990s Working Paper - Planning Commission (Planning Commission, 1990)
The Planning Commission’s working paper examines employment trends and prospects in India as the nation approached the 1990s, emphasizing employment generation as central to economic growth and poverty alleviation. Historical analysis reveals a slowdown in overall employment growth—from 2.82% (1972–78) to 1.55% (1983–88)—with urban employment outpacing rural, and a decline in organized sector job growth. Sectoral shifts indicate decreasing employment in agriculture and rising casual labor, while unemployment, particularly among women and urban populations, has increased. The report recommends an employment-oriented growth strategy integrating sector-specific measures: revitalizing agriculture through high-labor crops and irrigation, expanding rural non-agricultural activities, supporting small and medium enterprises, and enhancing skill development. Additionally, it suggests realistic employment targets, public sector job creation, and potential employment guarantee schemes. The study underscores the necessity of embedding employment goals within broader development policies to address structural labor market challenges and achieve near-full employment in the 1990s.
Planning Commission Government of India May 1990
Planning Commission Government of India May 1990
Keywords: Employment Trends; Unemployment; Rural Employment; Urban Employment; Organized Sector; Casual Labor; Underemployment; Employment-Oriented Growth; Skill Development; Public Sector Jobs; Labor Market; 1990s India; Economic Planning